Total civilian income in Northern Ireland - Cuthbert, Norman (Statistical and Social Inquiry Society of Ireland, 1951)
In recent years a good deal of the attention of economists has been devoted to regional problems. This has been largely due to the realisation that the mobility of factors of production (particularly labour) has been far from perfect and that consequently political units and economic units are not the same. The study of aggregates may fail to disclose the nature of the problems that affect the constituent parts, while the effects of a particular economic policy decided for the country as a whole may be very different in different regions. That these regional differences are of fundamental importance is amply demonstrated in the field of employment, for even in a situation of ?full? employment for an economy treated as a whole pockets of relatively heavy unemployment may continue to persist. Moreover, because of the general economic conditions within the region or because of the relationship of the region to the rest of the economy, employment may respond less readily to the Government's efforts to stimulate investment than might be expected from a study of the economy as a whole.
Read before the Society, 20 April 1951
Keywords: Regional analysis; Income analysis of Northern Ireland; Regional income measurement; 314.15